Seawater carbonate chemistry and locomotor behavior of sea cucumber Apostichopus japonicus - Liu, Botao; Huo, Da; Gaitan-Espitia, Juan Diego; Guo, Xueying; Yang, Hongsheng; Zhang, Libin (PANGAEA, 2025)
This study investigates the impact of combined stressors—ocean warming, acidification and hypoxia on the locomotion behavior of Apostichopus japonicus under future ocean scenarios. Cumulative movement distance, cumulative movement time, mean velocity, and maximum velocity of sea cucumbers were measured. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were extracted from tables in the related paper (see Related to) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-04-11.
Keywords: Animalia; Apostichopus japonicus; Behaviour; Benthic animals; Benthos; Coast and continental shelf; Containers and aquaria (20-1000 L or < 1 m**2); Echinodermata; Laboratory experiment; North Pacific; Oxygen; Single species; Temperate; Temperature